Makna Pendidikan Ekonomi Informal Dalam Perilaku Ekonomi Anak Dibingkai Nilai-Nilai Budaya Bugis - Andi Tenri Ampa; Supardi Salam; Andi Tonra Lipu; Andi Annisa Sulolipu (UIR Press, 2023)
The main aim of this research is to develop the meaning of economic education in children's economic behavior which is framed by cultural values so that when they grow up and become heads of families, they will have an effective and efficient economy. The approach in this research is a qualitative approach with descriptive methods. Data collection techniques in this research used interviews, observation and documentation. The subjects in this research were farming families in Rilau Ale District. The results of this research show that the economic education process for farming families in the Rilau Ale sub-district has formed children's economic behavior that reflects values and examples, including responsibility, trustworthiness, honesty, discipline and sincerity, as well as being diligent. Where these exemplary values are also found in the cultural values of the Bugis tribe which are very influential on siri culture, where the essence of siri', which is the value aspect of panngaderreng, is a form of culture that elevates human self-esteem and dignity in the social environment